Analyzing an Interactive Media English in Teaching Kindergarten - Nurfadila Narlis; Resma Nepi (Universitas Pahlawan Tuanku Tambusai, 2020)
This research is aimed at children who are actively involved in technology for educational reasons. Interactive media is considered as an inseparable part of the language learning process to support the efficiency of the learning process by taking into account the needs and achievements of students. Therefore, the application of the information and communication technology (ICT) curriculum in early childhood education is one of the efforts to develop the education sector to improve and support the learning, language and literacy of students with ICT. This descriptive research aims to describe learning English for Mathematics with ICT for kindergarten students. In addition, the description can be one of the basic forms of developing interactive learning based on student independent learning. In addition, this learning arrangement also aims to improve the learning habits and independence of students.